2018
DOI: 10.1088/1367-2630/aad2aa
|View full text |Cite
|
Sign up to set email alerts
|

Carrier-envelope phase controlled isolated attosecond pulses in the nm wavelength range, based on coherent nonlinear Thomson-backscattering

Abstract: A proposal for a novel source of isolated attosecond XUV-soft x-ray pulses with a well controlled carrier-envelope phase difference (CEP) is presented in the framework of nonlinear Thomsonbackscattering. Based on the analytic solution of the Newton-Lorentz equations, the motion of a relativistic electron is calculated explicitly, for head-on collision with an intense fs laser pulse. By using the received formulas, the collective spectrum and the corresponding temporal shape of the radiation emitted by a mono-e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…In equation (3) we have made use of the B = n L × E/c, connecting the magnetic induction and the electric field strength of a plane wave. As it is well known, the equations of motion (2)-(3) have a general analytic solution [29][30][31] and in [12] we determined an explicit particular solution of equations (2)-(3) for a laser pulse corresponding to equation (1) with k = 0. Using this solution, we are able to evaluate the spectrum of radiation emitted by an electron, which is given in the far-field by the following formula [32]:…”
Section: Theoretical Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…In equation (3) we have made use of the B = n L × E/c, connecting the magnetic induction and the electric field strength of a plane wave. As it is well known, the equations of motion (2)-(3) have a general analytic solution [29][30][31] and in [12] we determined an explicit particular solution of equations (2)-(3) for a laser pulse corresponding to equation (1) with k = 0. Using this solution, we are able to evaluate the spectrum of radiation emitted by an electron, which is given in the far-field by the following formula [32]:…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Since the frequency-dependence of the coherence factor equation (5) influences the spectrum of the collective radiation in an essential way [12], we plot the magnitude of C N (ω) in Figure 1 for electron nanobunches of different lengths. For each length, we plot |C N (ω)| both for a realistic electron nanobunch with stochastic electron positions characterized by a uniform distribution in the transverse direction and a Gaussian distribution in the longitudinal direction (solid lines), and for a rather artificial electron nanobunch with an equidistant spacing of electron positions (dashed lines).…”
Section: Theoretical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regime the process has been studied with regard to the laser strength parameter a 0 , the shape of the laser pulse both longitudinally and transversely [8][9][10][11][12], the bandwidth of the emitted radiation [13,14] and methods to reduce it [15]. In [16], it was shown that the phase of the field of the emitted radiation is linked to that of the laser pulse. Moreover, ref.…”
Section: Introductionmentioning
confidence: 99%